Experimental investigation and optimization of small-scale helium liquefaction with multi-cryocoolers. (July 2015) - Xu, Dong; Gong, Linghui; Li, Laifeng; Xu, Xiangdong; Liu, Huiming; Huang, Rongjin
Highlights: A serial–parallel-path helium liquefier with a liquefaction rate of 83 L/d using five 4 K G-M cryocoolers is developed. The additional purifier and precooling coil heat exchangers on the thinner part of the cold head cylinder containing the 2nd stage displacer could be removed to simplify the construction. The serial–parallel-path helium liquefier achieved a similar liquefaction rate as the parallel-path system. An optimum configuration is proposed and makes a reference to the design. Abstract: Small-scale helium liquefiers using regenerative cryocoolers with cooling power up to 1.5 W at 4.2 K could be used to re-liquefy evaporated helium gas of small- and medium-sized cryogenic devices such as MEG and PPMS. A serial–parallel-path helium liquefier with a liquefaction rate of 83 Litres per day (L/d) using five 4 K G-M cryocoolers is developed, and has been applied to the Wuhan National High Magnetic Field Center (WHMFC) in China. Different from parallel-path helium liquefier, the helium gas is effectively, stepwise precooled by heat exchangers on multi-cold flanges, and thus the additional purifier and precooling coil heat exchangers on the thinner part of the cold head cylinder containing the 2nd stage displacer could be removed to simplify the construction. Through theoretical calculation and conclusive analysis, an optimum configuration is proposed and makes a reference to the design of serial–parallel-path helium liquefier with multi-cryocoolers.